Understanding Organization-Customer Links in Service Settings - Schneider, Benjamin; Ehrhart, Mark G.; Mayer, David M.; Saltz, Jessica L.; Niles-Jolly, Kathryn (Academy of Management Journal, 2005)
We develop a framework of service-unit behavior that begins with a unit's leader's service-focused behavior and progresses through intermediate links (service climate and customer-focused organizational citizenship behavior) to customer satisfaction and then unit sales. Data from a sample of 56 supermarket departments provide at least moderate support for our mediational hypotheses. We discuss findings with a particular focus on the relationship between internal organization functioning and external effectiveness in service settings. In addition, several issues related to testing for mediation using quantitative analysis are identified and discussed.